EFFECTS OF METFORMIN ON THE WEIGHT OF HEALTHY AND STREPTOZOTOCIN-INDUCED DIABETIC ANIMAL MODEL - Ali, Akhtar; Shaheen, Shehla; Zahid, Nisha; Zafar, Urooj; Ahmed, Farah; Farooq, Lubna (Journal of Ayub Medical College Abbottabad, 2021)
Background: Metformin was approved by FDA in 1994 for the treatment of type II diabetes mellitus. Due to its interaction with the AMP kinases enzyme system, it showed multiple effects on other organ systems of the body. Despite being the drug of the first choice for type II diabetes it became a popular drug for PCOS and currently, various trials are proving its anticancer effects. Though not approved by FDA it is also responsible for weight loss. The study aims to investigate the effect of metformin on the weight of healthy and streptozotocin-induced diabetic animal models. The study was performed at Animal House, Faculty of Pharmacy Ziauddin University Karachi. Methods: It was a pre-clinical experimental study conducted at Ziauddin University Karachi from August 2019 to December 2019. 36 male Albino rats were divided into 6 groups such with 6 rats in each group. Out of six three were healthy models (i.e., groups 1, 2, and 3) and the remaining three were diabetic models (i.e., Group 4, 5, and 6). Diabetes was induced in groups 4,5 and 6 by using the diabetogenic drug Streptozotocin. In Group 1 and 4, 0.5 ml normal saline was administered, 50 mg/kg (5 mg/100g) metformin diluted in 0.5 ml distilled water was administered in Group 2 and 5 followed by administration of 80 mg/kg (8 mg/100g) metformin diluted in 0.5ml distilled water in Group 3 and 6. the protocol was followed twice a day for 42 days. The weight of all the groups was calculated before and after drug intervention. Results: Metformin-induced weight loss was observed in healthy treated groups at both doses, however, there was no significant difference in weight loss in diabetic treated and untreated groups. Conclusion: Metformin showed weight lowering properties in healthy treated subjects, after induction of diabetes we found weight loss in diabetic untreated and treated groups which suggests that hyperglycemia may cause weight loss but when metformin corrects the hyperglycemic profile it does not lead to an increase in weight.